Cooperation and collapse in a communal livestock production SES model – A case from South Africa. (January 2016) - Rasch, Sebastian; Heckelei, Thomas; Oomen, Roelof; Naumann, Christiane
Abstract: Institutional arrangements are considered necessary for successfully governing the commons. They are considered to be most effective if they are self-organized rather than imposed from outside. However, endogenous institutional arrangements, such as local norms, are specific to a particular socio-ecological system (SES). This paper presents a SES model of communal livestock producers in South Africa. Its bio-physical component accounts for the impact of biotic and abiotic factors on livestock population. The social agent-based component models individual and socially determined behaviour, the latter of which is a social norm specific to the case. Model results show that when cooperative agents obey and sanction the norm, there is less likelihood of SES collapse in terms of livestock population crashes. However, cooperation among agents only emerges in times of ecological crisis where social reorganization is fostered. The crisis creates an opportunity for initializing a self-enforcing process of mutual cooperation. Model specifications are based on survey data, and agents were parameterized according to individual household data. A sensitivity analysis shows that this empirical heterogeneity cannot be reduced without changing model outcomes. Highlights: We model a communal cattle production SES in South Africa to investigate the impact of a social norm. The SES model is a full integration of an ABM with a dynamic rangeland model. The emergence of norm compliance prevents SES collapse. A SES crisis is the opportunity for cooperative behaviour to emerge. The model is sensitive towards the parameterization of agent attributes from field data.